A Vila Santa Isabel na Avenida Afonso Pena: a experiência positiva da moradia popular em região central de Belo Horizonte - Tatiana Soledade Delfanti Melo (2012)
The Santa Isabel Village on Afonso Pena Avenue is a slum with reducedpopulation and area. It is reminiscent from Pindura Saia, a much larger slum that took place in the hill around the Water Reservoir in Cruzeiro district in the 30s, a distant and peripheral area of the city at that time, currently a valued central area. The almost complete extinction of Pindura Saia Slum occurred in the 70's, under the existing Policy Eradication of Slums performed by the CHISBEL Municipal Agency. This research focuses on social relations between residents from Santa IsabelVillage and residents from neighborhoods of its immediate surroundings. These relationships were verified based on questionnaires sent to each of the two social groups that co-inhabit the region. The experience of public housing on Afonso PenaAvenue was positive in several aspects. One of them was found in sociospatial interaction, as opposed of segregation, between slum dwellers and residents from neighborhood. Another aspect refers to the opportunities of access to social constitutional rights that Vila Isabel slum dwellers have based on the location of their house, such as work, education, health, leisure and security. There are no requirements to justify the removal of Santa Isabel Village performed by URBEL, in other words, it is neither in the middle of the road, nor in hazardous area, it is urbanized and it is located in municipal public property. However,land use regulation as recommended by the "new legal-urban order" is not contemplated by the Municipal Government. The future prospects in view of the historical treatment of the slums and the current trends of Policy Intervention in slums in Belo Horizonte point to the extinction of the Village and the enclosed area as a Zone of Special Social Interest that it occupies. The positivity of this experience may not be experienced by future generations, indicating the retreat of practice in relation toadvanced legal discourse of the Brazilian Democratic Institution.